MECHANISMS FOR DEVELOPING PROFESSIONAL-METHODICAL COMPETENCE OF TEACHERS OF PRESCHOOL EDUCATIONAL ORGANIZATIONS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article discusses the development mechanisms of professional methodological competence among preschool education institution educators. The concept of competence and its structural components are analyzed. Special attention is paid to the term “mechanism,” its meaning in the pedagogical context, and practical application methods aimed at improving the methodological readiness of preschool teachers.